PENGENALAN PEMBUATAN LAPORAN LABA RUGI PADA UKM VEZARA COLECTION - Yusbardini (Transpublika Publisher, 2022)
For small and large businesses, financial reports are very important. By examining the available financial reports, strategic business development decisions can be made. Because they find creating financial reports difficult and time consuming, small business owners often overlook this. Big businessmen who have carefully completed financial reports are exempt from this. Businessmen can determine the state of the company and whether it is making a profit or loss from the income statement. MSMEs will find it easier to decide on strategies to achieve profit goals and increase business efficiency and effectiveness if they use income statements. The purpose of this community service activity is to increase knowledge about the importance of income statements for MSMEs and the stages in making profit and loss reports so that partners really understand making profit and loss reports. This activity was carried out by the MSME partner VEZARA COLLECTION, located at the Cililitan Glosir Center, East Jakarta. The implementation is carried out using Zoom, which is attended by partner owners, and by the community service team, which is carried out on holidays. The results of this community service activity can run optimally according to the targets set and in accordance with the objectives of the community service.